N3,N7-diaminophenothiazinium derivatives as antagonists of α7-nicotinic acetylcholine receptors expressed in Xenopus oocytes - Sadek, Bassem; Petroianu, Georg (Pharmacological research, 2012)
Derivatization of phenothiazine (PTZ, 1) has been a commonly used method to develop drugs with various pharmacological properties. In the present study, a series of PTZ derivatives 1-11 were investigated on the inhibition of the cloned α7 subunit of the human nicotinic acetylcholine receptor (α7-nAChR) expressed in Xenopus oocytes by using the two-electrode voltage-clamp technique. In the first series of experiments, the effect of unsubstituted phenothiazine 1 on α7-nAChRs was compared with that of the N3,N7-diaminophenothiazin-5-ium derivative 2, and of sequentially methylated derivatives 3-6. In the second set of experiments, the effects of N3,N7-tetra-ethyl- to n-hexylphenothiazin-5-ium derivatives 7-11 were tested. Despite the lack of activity found for 1, a reversible inhibition of α7-nAChRs, ranging from moderate to potent, was observed as a result of a sequential amine- and methylamine substitution of 1. The inhibition of ACh (100μM)-induced currents was concentration-dependent with IC50 values ranging from 0.4 to 16.8μM. However, an optimal inhibitory activity was achieved by prolongation of alkyl chains up to propyl size, as found in PTZ derivative 8, whereas further lengthening of alkyl chains to n-butyl-, n-pentyl-, or n-hexyl groups resulted in inactive derivatives 9-11. The results evidently suggest the presence of a lipophilic binding pocket of narrow tolerability on the receptor protein. These results emphasize the importance of amine and/or alkylamine moieties for the inhibitory effect of PTZ derivatives and provide further insights for the development of novel antagonists targeting α7-nAChRs.